"How Foraging Works": Let's not forget the physiological mechanisms of energy balance. (2019) - Smulders, Tom V.; Boswell, Timothy; Henderson, Lindsay J.
Abstract: Anselme & Güntürkün propose a novel mechanism to explain the increase in foraging motivation when experiencing an unpredictable food supply. However, the physiological mechanisms that maintain energy homeostasis already control foraging intensity in response to changes in energy balance. Therefore, unpredictability may just be one of many factors that feeds into the same dopaminergic "wanting" system to control foraging intensity.